THE MODERN ASPECTS OF SURGERY TREATMENT OF PATIENTS WITH GENERALIZED PARODONTITIS - Проць, Г. Б.; Пюрик, В. П.; Ничипорчук, Г. П.; Солоджук, Ю. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The scientific work is devoted to the research of paculiarities of bone replacing material usage. This material was enriched by active osteotropic component (surrogate), during the flap operations of patients with generalized parodontitis. The results of osteodentrometrical explorations and the results of bone remodelling markers usage explorations are set during surgery treatment in 160 patients. It is discovered, that the surgery treatment of the parodontical tissues in 46 % of the patients was done on the background of low level of mineral density of bone tissue. While planning the surgery treatment of the patients with generalized parodontitis, it is important to study the markers of bone tissue remodelling in order to evaluate the structural and functional state of bone tissue and to differentially prescribe osteotropic drugs. This will enhance the positive fluency of after-surgeon period and the insurance the absence of complications. The results show, that flap operations combined with the bone brain usage and the usage of osteoplastic materials, activate the process of regeneration of the bone tissue of alveolar outgrowth and of the connective tissue attachment. These operations also refine the anatomical-functional results of the patients with generalized parodontitis.